Mouse Ovarian Cancer Models Recapitulate the Human Tumor Microenvironment and Patient Response to Treatment - Maniati, Eleni; Berlato, Chiara; Gopinathan, Ganga; Heath, Owen; Kotantaki, Panoraia; Lakhani, Anissa; McDermott, Jacqueline; Pegrum, Colin; Delaine-Smith, Robin M.; Pearce, Oliver M.T.; Hirani, Priyanka; Joy, Joash D.; et al. (Cell Reports, 2020)
Maniati et al. show how orthotopic transplantable mouse ovarian cancers with appropriate genotypes develop microenvironments that replicate many features of human primary ovarian tumors and metastases. Molecular features of the mouse tumors combined with machine learning may allow the identification of patients who are most likely to respond to specific therapies.
CRIS-Team Scopus Importer:2020-01-24
Keywords: matrisome; mouse model; ovarian cancer; serous; tumor microenvironment